ANALYSIS OF EFFICIENCY ON RICE FARMING - Rita Hanafie; Mashudi Heryono; Iwan Nugroho (Agricultural Socio-Economics Journal, 2016)
The research aims to analyze the efficiency on rice farming business and factors that affect rice production associated with participation in farmer groups. The research was conducted in Senduro Village, Senduro District, Lumajang Regency. Analysis method in this research included revenue, cost and efficiency on rice farming, as well as multiple regression of production function. The results show that there are different performance among farmers who are member and non-member of farmer’s group. Productivity to the farmers who are member of farmer group was 8.776 tons per hectare and non-member was 7.275 tons per hectare. Farmers in the group gained higher revenue (IDR 37.74 million per hectare) compared to non-member (IDR 31.28 million per hectare). Production cost to the farmers who are member of farmer group reached IDR 12.69 million per hectare and non-member was IDR 12.55 million per hectare, with efficiency values (R/C) 2.97 and 2.49, respectively. Farmers who become member of the group adhered better farming practices which use more efficient fertilizer, more intensive irrigation and more seeds. Rice production is significantly affected by land size and the group membership. Ten percent increasing in land size would increase production by 2.4 percent. However, for the other factors, i.e, age, education, number of family member, seeds, manpower and fertilizer had no significant effect on rice production.